Incorporating Digital Media Platforms to Enhance Sustainability Insights in the UI GreenMetric World University Rankings Network - Junaidi Junaidi; Riri Fitri Sari; Yovita Yiwananda Yamin; Sabrina Hikmah Ramadianti; Jauzak Hussaini Windiatmaja; Yogi Andrian Sidianto (Journal of Sustainability Perspectives, 2024)
Conventional ways of delivering sustainability content often fail to capture the breadth and dynamism of university challenges. To overcome the issue, UI GreenMetric has proposed a new way of delivering content by using digital media. This study investigates the integration of digital mediaincluding Instagram, YouTube, Facebook, and Website to augment sustainability insights within the UI GreenMetric World University Rankings Network. This study analyzes the results, effects, and further implications of UI GreenMetric’s practices in incorporating user-generated content from those digital media platforms into the sustainability assessment framework to leverage the ubiquity and the richness of the content. The analysis is conducted for various activities, such as podcast/live discussions, event streaming, posts and videos related to sustainability initiatives. The findings show that integrating digital media has significantly boosted sustainability outreach within the UI GreenMetric network. UI GreenMetric not only drives the transformation of individuals, communities, and universities toward sustainability but also extends its impact through dozens of online events, such as webinars, workshops, courses, live discussions, and podcasts throughout the year. These efforts have successfully reached a wider audience, leading to meaningful behavioral changes as participants engage in campaigns and actively contribute to rankings and events.